Identifying a guiding list of high involvement practices in human resource management - M Rosario Perello-Marin; Gabriela Ribes-Giner (WPOM : Working Papers on Operations Management)
In today global competitiveness, it is becoming increasingly frequent, the introduction of new management practices to organizations, seeking to enhance performance as a form of Management Innovation (MI). This is so because such practices are usually difficult to replicate exactly from one company to another, provided they are well rooted in the daily work in the organization. The main purpose of this paper is, by reviewing the previous work done in this area, to present a general list of Human Resource Practices (HRM practices) geared towards improving organizational effectiveness and hence better performance outcomes. Many work has been done to date within this topic, but it is difficult to find a consensus about the best way to address to this practices, and this fact makes difficult to compare different studies and their results. We present a detailed but synthesized list of those HR practices to be used as a starting point in any sector whether industrial or services